Segurança em redes industriais: aplicação da técnica de autenticação HB-MP* em rede Modbus - Fagundes, Frederico Duarte (2022)
The growth in the integration and use of standards and protocols common to computer networks has seen industrial networks increasingly subject to attacks and invasions. Modbus is an example of a widely used industrial protocol, and like others, does not possess native tools for secure communication. Security for Modbus is achieved generally by use of security techniques on the lower layers of the communication stack. This study highlights vulnerabilities associated with Modbus, with its focus on Modbus TCP, while offering a protection proposal through use of Master and Slave authentication at the application layer level. The technique was implemented with the HB-MP* protocol, which focused on protection against invading Masters or Slaves. The main contribution of this paper is found through providing Modbus communications greater security at the application layer level, as a single security implementation or increasing security in conjunction with other lower layer security techniques. A Modbus TCP network was set up with Master and Slave nodes performing Modbus communication with HB-MP* authentication, subject to different intrusion scenarios. Results showed it was possible to detect invading nodes and prevent some attacks, whereas suffering only a small cost associated with processing and transmission delays.